A brief peer gatekeeper suicide prevention training: Results of an open pilot trial. Issue 7 (2nd February 2018) - Rallis, Bethany A.; Esposito‐Smythers, Christianne; Disabato, David J.; Mehlenbeck, Robyn S.; Kaplan, Seth; Geer, Leslie; Adams, Ryan; Meehan, Barbara
Abstract: Objective: The purpose of the present study was to test a 1‐hour peer suicide gatekeeper training for students from the broad college community in the context of an open pilot trial. Method: Two‐hundred and thirty‐one college students were recruited university‐wide, M age  = 20.7, 65.4% female, and completed a peer suicide prevention gatekeeping training program. Assessments were completed at pre‐training and post‐training as well as 3‐month follow‐up. Results: This brief peer suicide gatekeeper training program was associated with increases in suicide prevention knowledge. It was also associated with an increase in the number of students who identified suicidal youth and made mental health referrals, as well as total number of referrals made, over the course of three months. Females reported greater improvement in suicide prevention skills and knowledge post‐training than males. Conclusions: Offering peer suicide gatekeeper training to students from the general college population may hold promise in suicide prevention efforts.